Mecmûa-i ulûm-i riyâziyye - İshak Efendi, Başhoca, ?-1836. (İstanbul İstanbul İstanbul)
4 c. (1. c. [15], 512 s., [6] katlı şekil ; 2. c. [1], 486, [18] katlı şekil ; 3. c. 8, [4], 649 s., [15] katlı şekil ; 4. c. [2], 536 s., [7] katlı şekil)